Controlled Oxidation of Metallic Molybdenum Patterns via Joule Heating for Localized MoS2 Growth - Norah Aldosari; William Poston; Gregory Jensen; Maryam Bizhani; Muhammad Tariq; Eric Stinaff (Nanomaterials)
High-quality two-dimensional transition metal dichalcogenides (2D TMDs), such as molybdenum disulfide (MoS2), have significant potential for advanced electrical and optoelectronic applications. This study introduces a novel approach to control the localized growth of MoS2 through the selective oxidation of bulk molybdenum patterns using Joule heating, followed by sulfurization. By passing an electric current through molybdenum patterns under ambient conditions, localized heating induced the formation of a molybdenum oxide layer, primarily MoO2 and MoO3, depending on the applied power and heating duration. These oxides act as nucleation sites for the subsequent growth of MoS2. The properties of the grown MoS2 films were investigated using Raman spectroscopy and photoluminescence measurements, showing promising film quality. This study demonstrates that Joule heating can be an effective method for precise control over TMD growth, offering a scalable approach for producing high-quality 2D materials that have the potential to be integrated into next-generation electrical and optoelectronic technologies.